Upgrading work and improving facilities for Bengkel Usahawan Asas Tani (IAT), Jabatan Pertanian Negeri Selangor / Muhammad Muaz Mohd Asri - Mohd Asri, Muhammad Muaz (2018)
This report is content all about the information about my case study through practical training under company JKR Selangor during the four months of practical training. The topic that I have choose to complete my practical training report is upgrading work on existing building on agro-based industry workshop because I have been given instruction by my supervisor at JKR Selangor to handle the project I really appreciate because have been given the opportunity to handle a project This report has a 5 chapter which included all information about the company, general information about case study, information about case study which is focus on specific topic that I have choose, and also problems and recommendation that have been analysed. The first chapter in this report is detail of information of the company. In this chapter, all the general information about the background of the company and the organization that owned by company that I choose to undergo the practical training. It also content about the scope of work about this company, objective, mission, vision, location, and also panel company which is involved with the company JKR Selangor. The second chapter give out information about the literature review based on my case study. All the general information and overview about the topic that I have choose is included in this chapter. It content about the definition, types and etc. The third chapter list out all the information about my case study that have get from my observation and learning with my real experience at the site that I have involved under JKR Selangor. It Content about the specific information that I get through practical training.